An event mixing technique for Bose-Einstein correlations of two pions in photoproduction around 1 GeV*Supported by Ministry of Education and Science of Japan (19002003) and JSPS KAKENHI (24244022, 26400287). (November 2016) - He, Qing-Hua; Fujimura, H.; Fukasawa, H.; Hashimoto, R.; Honda, Y.; Ishikawa, T.; Iwata, T.; Kaida, S.; Kasagi, J.; Kawano, A.; Kuwasaki, S.; Maeda, K.; et al.
Abstract: We have developed an event mixing technique to observe Bose-Einstein correlations (BEC) between two identical neutral pions produced in photo-induced reactions in the non-perturbative QCD energy region. It is found that the missing-mass consistency cut and the pion-energy cut are essential for the event mixing method to effectively extract BEC observables. A Monte Carlo (MC) simulation is used to validate these constraints and confirms the efficiency of this method. Our work paves the way for similar BEC studies at lower energies where the multiplicity of emitted bosons is limited.